Are Development Goals Enough to Attract Foreign Direct Investment? - Gülcü, Yunus (My University, 2024)
This study investigates whether development goals contribute to economic growth in countries with the highest share of foreign direct investment in the world economy. It is concluded that there is cross-sectional dependence and unit root at level value in foreign direct investment, gross domestic product and sustainable development index. Since there is a long-run relationship in the model, a panel vector error correction model is constructed. In the short run, there is no causality from gross domestic product and sustainable development index to foreign direct investment. However, in the long run, such causality is obtained. On a country basis, there is causality from Sustainable Development Goals to FDI in Estonia, Finland and Germany. In Japan, Poland, Colombia, Latvia, Finland and Slovak Rep. there is causality from Gross Domestic Product to FDI. These findings suggest that long-term strategic planning and development goals play a critical role in attracting foreign capital. Moreover, analyzing the effects of different countries' emphasis on development goals and economic structures on foreign capital attraction provides important clues for future policy-making processes.
Keywords: Panel Data; Foreign Direct Investment; Sustainable Development Index